The Geopolitics of Energy System Transformation - Bradshaw, Michael (Bristol University Press, 2026)
Available open access digitally under CC-BY-NC-ND licence. Our global energy system needs radical and speedy transformation in order to meet climate change targets. This shift is currently conceived in two ways: a ‘high carbon transition’ away from fossil fuels and a ‘low carbon transition’, the development of a low carbon energy system. This accessible book guides us through the 'messy mix', the perilous ground that sits between the present and the future energy systems. Evidence-based and solutions-focused, this is a novel framework to help manage geopolitical challenges and enable a swift, just, orderly and equitable transition away from fossil fuels.